Synthesis of silica and carbon nanoparticles from rice husks for latent fingermarks application - A/P Rajan, Revathi (2018)
Research into latent fingermark developing techniques has taken many paths over the years as researchers and practitioners explore numerous methods to enhance existing powders and reagents. Currently, copious research is being dedicated to investigating the transformational improvements that could be provided by nanosized compounds to expand the sensitivity and selectivity of fingermark dusting powders to develop fingermarks with high clarity and better contrast. Nonetheless, such a technique has inherent drawbacks of limited field applicability, cost and energy intensive, incurs health hazard to the users in the long run as well as prepared using synthetic precursors. In this research novel synthesis techniques of silica nanoparticle (SiNP) and carbon nanoparticle (CNP) from a sustainable eco-friendly source, rice husk (RH) was developed. Acid digestion process was conducted to remove trace metal impurities from RH. The filtrand was ashed to extract silica, while the filtrate was aged to form CNP, a novel CNP synthesis technique pioneered in this research. Sodium silicate was formed by dissolving highly pure rice husk ash, obtained from the stepwise purification of RH, in alkali solution. Precipitation of SiNP using acetic acid and acetone is introduced in this research to form minimally agglomerated, well dispersed spherical SiNP with a mean particle size of 270 nm, verified using imaging techniques. Silica chemical composition and amorphous nature were confirmed by using spectroscopic analysis. Freeze-drying produced mesoporous pore volume (0.167 cm3/g) silica powders with a 4.2 nm average pore size (0.9 to 57.9 nm pore sizedistribution) and very high specific surface (162.00 m2/g (Brunauer-Emmett Teller, (BET) and 238.60 m2/g Barrett-Joyner-Halenda (BJH)). Ageing of the filtrate from acid digestion produced amorphous CNP that exhibited non-smooth, slightly irregular spherical particles with a higher degree of agglomeration in comparison to SiNP. Particle size distribution fell in the range of 100 to 500 nm with mean particle size of 300 nm. Molecular bonding and chemical composition of the CNP was confirmed using spectroscopic techniques. CNP powder possessed microporous pore volume (0.009 cm3/g) with a 61.75 nm average pore size (0.89 to 81.90 nm pore size distribution) and low surface area value (0.558 m2/g BET and 4.816 m2/g BJH). Spherical SiNP obtained was formulated into three derivative products namely white nanoparticle powder, nanoparticle reagent (NPR) and multicoloured nanoparticle powder, while the CNP powder was used as the black nanoparticle powder. A methodological approach was conducted to compare the efficiency of the nanoparticle products against commercial products by developing fresh and aged fingermarks of various stages. Standard scoring system was applied to evaluate the results and statistical analysis was employed to summarise the data. Findings revealed that the nanoparticle powders and reagent performed on par with the existing commercial powders while exhibiting higher selectivity. Nanoparticle synthesis from low cost precursor in this research did not require special equipment, addition of resins/adhesives or surface passivation. Additionally, utilisation of RH may boost farmer’s income and incorporate non-toxic green nanotechnology into routine investigative procedures. In conclusion, the low cost products developed exhibited promising quality and superiority to the existing products in the market.